Sleep continuity, stability and organization in good and bad sleepers. (October 2021) - Conte, Francesca; Cerasuolo, Mariangela; Fusco, Giuseppina; Giganti, Fiorenza; Inserra, Iginio; Malloggi, Serena; Di Iorio, Ilaria; Ficca, Gianluca
The relationship between objective and subjective sleep quality is still debated. Here, we investigate differences in objective sleep parameters in habitual subjective good sleepers and bad sleepers with the aim of evaluating sleep continuity, stability and organization as possible determinants of subjective sleep quality. In total, 38 subjects (good sleepers, N  = 18; bad sleepers, N  = 20) underwent two nights of sleep recording. Traditional sleep parameters displayed no between-groups differences. Conversely, bad sleepers showed lower sleep continuity (awakenings frequency), stability (e.g. arousals and state transitions frequency) and organization (e.g. number of sleep cycles and time spent in cycles). Our findings point to the involvement of these measures in determining habitual sleep quality perception and suggest the possibility to include them in standard sleep assessments.